2012
DOI: 10.1055/s-0032-1329231
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Outcome of Autologous Chondrocyte Implantation: A Systematic Review

Abstract: Autologous chondrocyte implantation (ACI) is an effective method of treatment of chondral defects of the knee. ACI outcomes are influenced by patient-, knee-, and lesion-specific factors. We compiled subject-level data from current studies on ACI and quantitatively analyzed this data set for associations between patient-, knee-, and lesion-specific factors and the outcome of ACI surgery. A systematic review of studies investigating ACI treatment outcomes in the knee was performed. Only studies that published s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 41 publications
(49 reference statements)
2
40
1
1
Order By: Relevance
“…Behery et al 83 reviewed 12 case series with 270 knees and found that none of age, gender, duration of symptoms and lesion size significantly predicted outcomes. They noted successful use of ACI in patients aged over 50 years in three studies.…”
Section: Clinical Effectivenessmentioning
confidence: 99%
“…Behery et al 83 reviewed 12 case series with 270 knees and found that none of age, gender, duration of symptoms and lesion size significantly predicted outcomes. They noted successful use of ACI in patients aged over 50 years in three studies.…”
Section: Clinical Effectivenessmentioning
confidence: 99%
“…As with other cartilage repair techniques, younger patients with more localized lesions tend to do better [118][119][120].…”
Section: Autologous Chondrocyte Implantationmentioning
confidence: 96%
“…Throughout the rehabilitation program, promotion of proper muscle activation, joint mechanics, and technique with minimal compensation patterns during all exercises and activities is likely important to optimize muscle performance and normalize joint-loading strategies following articular cartilage procedures in the knee. 5,8,28 and therefore were not a focus of our search. To the best of our knowledge, this is the first systematic review to evaluate functional performance following cartilage procedures.…”
Section: Implications For Rehabilitation: Joint Loadingmentioning
confidence: 99%
“…[ research report ] capacity during activities of daily living (eg, 6-minute walk test) or to evaluate performance during higher levels of activity (eg, single-leg hop tests). Outcomes following articular cartilage surgical procedures related only to patient-reported outcome measures have been summarized in previous reviews 5,8,28 and therefore were not a focus of our search. To the best of our knowledge, this is the first systematic review to evaluate functional performance following cartilage procedures.…”
Section: Implications For Rehabilitation: Joint Loadingmentioning
confidence: 99%
See 1 more Smart Citation